Effects of Vaccinium-derived antioxidants on human health: the past, present and future - Ghosh, Amrita; Debnath, Samir C.; Igamberdiev, Abir U. (Frontiers in Molecular Biosciences, 2024)
Dietary intake of Vaccinium berries has demonstrated significant potential in preventing many risk factors associated with metabolic syndromes in the human population. In recent years, a multitude of research has shown the role of antioxidants derived from Vaccinium berries on chronic diseases such as cardiovascular disorders, diabetes, obesity, and cancer. Several studies have also investigated the effect of Vaccinium berry consumption on their ability to modulate the risk factors associated with oxidative stress, vascular function, inflammation, and lipid metabolism. Regarding cancer, studies showed that the consumption of berries reduces inflammation, inhibits angiogenesis, protects against DNA damage within the cell, and controls apoptosis and proliferation rates in malignant tumours. However, which components are responsible for the health benefits is still unclear. Reports show that whole berry consumption usually confers positive effects on human health, and the health-promoting potentials are likely due to the presence of polyphenols with antioxidant activities. Among these polyphenols, various Vaccinium berry species have been reported to contain anthocyanins and flavonoids. These two polyphenolic compounds are known to have higher antioxidant activity and are beneficial for human health. There are now several studies and human clinical trials documenting the beneficial effects of Vaccinium berries, and these findings suggest that they may be promising for preventing and treating neurodegenerative diseases. This review focuses primarily on dietary Vaccinium berries consumption effects on human health and their potential role as therapeutic agents.